2003
DOI: 10.1016/s1097-2765(03)00142-4
|View full text |Cite
|
Sign up to set email alerts
|

Y14 and hUpf3b Form an NMD-Activating Complex

Abstract: Messenger RNAs with premature translation termination codons (PTCs) are degraded by nonsense-mediated mRNA decay (NMD). In mammals, PTCs are discriminated from physiological stop codons by a process thought to involve the splicing-dependent deposition of an exon junction complex (EJC), EJC-mediated recruitment of Upf3, and Upf2 binding to the N terminus of Upf3. Here, we identify a conserved domain of hUpf3b that mediates an interaction with the EJC protein Y14. Tethered function analysis shows that the Y14/hU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
307
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(321 citation statements)
references
References 51 publications
13
307
0
1
Order By: Relevance
“…Surprisingly, these motifs exhibited 23% and 38% identity (38% and 57% similarity) to a UPF3b C-terminal motif, which is known to mediate binding to the EJC (Fig. 3A,B; Gehring et al 2003;Kunz et al 2006;Buchwald et al 2010). We therefore termed these motifs EBMs, or EBM1 and EBM2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Surprisingly, these motifs exhibited 23% and 38% identity (38% and 57% similarity) to a UPF3b C-terminal motif, which is known to mediate binding to the EJC (Fig. 3A,B; Gehring et al 2003;Kunz et al 2006;Buchwald et al 2010). We therefore termed these motifs EBMs, or EBM1 and EBM2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Closer examination, however, revealed that this region does contain two short sequence motifs that are conserved. These motifs are related to the EBM found in the C terminus of the NMD factors UPF3a and UPF3b (Gehring et al 2003;Buchwald et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmids with high purity for mammalian cell transfection were prepared with a Maxiprep kit (Qiagen). Double tethering reporter pmirGlo-Ptight-2BoxB-2MS2: 2BoxB-2MS2 sequence was designed as follows: 5′-CTC- [37,38], synthesized, and PCR amplified and cloned to 3′-UTR of F-Luc in pmirGlo-Ptight vector reported [12] (NheI, SbfI; forward primer, 5′-ATACGCTAG-CCTCGACTAAGTCCAACTACTAAACTGGG-3′; reverse primer, 5′-GTATCCTGCAGGTTAGGATCTAATGAACCCGG-GAATACTG-3′).…”
Section: Plasmid Constructionsmentioning
confidence: 99%